Asymptomatic flow of Rosai-Dorfman disease - Petrović Dragan; Mihailović Dragan; Petrović Slađana; Živković Nikola; Mijovićć Žaklina; Bjelaković Bojko; Kostić Miloš; Kesić Ljiljana; Stanković Ana; Petrović Milica; Vučković Ivica (Vojnosanitetski Pregled)
Introduction. Sinus histiocytosis with massive lymphadenopathy is a rare benign self-limiting disease of unknown etiology. The salivary gland involvement, indicating the extranodal character of the disease, often presents a diagnostic dilemma requiring immunohistochemical staining of surgically removed tumor to confirm the diagnosis. Case report. We report a 43-year-old man presented with an asymptomatic mass in the left mandibular angle. On physical examination, the lesion was described as a painless, mobile, firm-elastic consistency nodule, which measured 4 × 3 cm in diameter, with normal overlying skin. A mass with the same characteristics, dimensions 2 × 2 cm, was also noted in the right parotid region. No other changes in regional lymph nodes were detected. On macroscopic examination the lesion was firm, multilobulated, yellowish and rounded, while on microscopic examination the lesion was composed almost entirely of polygonal histiocytes with abundant cytoplasm, emperipolesis, plasma cells arranged in sheets, and lymphocytes scattered or within clusters. The observed histiocytes were found to be CD68 and S100 protein positive. Conclusion. Rosai-Dorfman disease is a beningn and frequently overlooked clinical and pathological entity that may be misinterpreted as a neoplastic disease. [Projekat Ministarstva nauke Republike Srbije, br. 41017]